MENATA MASA DEPAN INDONESIA EMAS 2045 DALAM BINGKAI LIFELONG LEARNING DAN UNIVERSAL EDUCATION (Jurnal Ilmiah PENDAS: Primary Educational Journal, 2023)
This research aims to determine Indonesia's preparations in facing the future of a golden Indonesia in 2045. The problem formulation of this research is the application of lifelong learning and universal education in facing a golden Indonesia in 2045. This research uses a literature study research method. From the results of the discussion, it was found that in facing Indonesia's planning towards Indonesia's golden era in 2045, the key is to prepare in education by having the concept of lifelong learning and universal education which must be understood by students in learning strategies at school.
Keywords: Indonesia emas, belajar sepanjang hayat, pendidikan universal